Propanol and 1, 3-propanediol enhance fatty acid accumulation synergistically in Schizochytrium ATCC 20888 - Wang, Tiantian; Wang, Fangzhong; Zeng, Lei; Guo, Pengfei; Wu, Yawei; Chen, Lei; Zhang, Weiwen (Frontiers in Microbiology, 2023)
The effects of propanol and 1, 3-propanediol on fatty acid and biomass accumulation in Schizochytrium ATCC 20888 were explored. Propanol increased the contents of saturated fatty acids and total fatty acids by 55.4 and15.3%, while 1, 3-propanediol elevated the polyunsaturated fatty acids, total fatty acids and biomass contents by 30.7, 17.0, and 6.89%. Although both of them quench ROS to increase fatty acids biosynthesis, the mechanisms are different. The effect of propanol did not reflect on metabolic level while 1, 3-propanediol elevated osmoregulators contents and activated triacylglycerol biosynthetic pathway. The triacylglycerol content and the ratio of polyunsaturated fatty acids to saturated fatty acids were significantly increased by 2.53-fold, which explained the higher PUFA accumulation in Schizochytrium after adding 1, 3- propanediol. At last, the combination of propanol and 1, 3-propanediol further elevated total fatty acids by approximately 1.2-fold without compromising cell growth. These findings are valuable for scale-up production of designed Schizochytrium oil for various application purposes.